Assessment of heart rate in infants from 6 to 36 months old during aquatic activities - Martins, Marta (2011)
Some authors (e.g. Maclaren and Coulson, 1999; Dekerle, 2006) reported that aerobic training has a positive effect on critical velocity in swimming. However, it raises the question whereas this effect is similar among swimmers of different performance level. Therefore, the purpose of this study was to determine the training responses in aerobic parameters (critical velocity and critical stroke rate) in young swimmers of different level during an in-season period of training.